Pelatihan Pengolahan Alat Ungkap Masalah (AUM) Dengan Menggunakan Komputer Bagi Konselor Sekolah SMKN 62 Lenteng Agung - Natalia Evianti; Rino Subekti; Boy Firmansyah (Jurnal Pengabdian Teratai, 2020)
Information technology era nowadays has brought challenges for counselor to participate and master it. Therefore, counseling is not only face-to-face in a closed room, but can be done through a remote format. The counselor uses the information media as a tool in carrying out his duties, which is hereinafter known as e-counseling service. The real form of the application of e-counseling is the emergence of online counseling services, through websites of online counseling service providers, or, more simply, counseling is done by telephone, mobile phone and / or through personal email and several application programs for chatting such as Skype, WhatsApp and so on. Also, the use of other application programs that support the implementation of the duties of the counselors, such as the emergence of the Problem Identification Tool (AUM) processing application program. So far, school counselors have been administering AUM and processing it manually, so it is time consuming and inefficient. To help the counselors, finally the Instrument Development Team with the permission of the AUM instrument drafting team took the initiative to develop an AUM application program based on the Microsoft Access program, the e-counseling technology in this program allows displaying more information regarding respondent problems, in this case especially students who later can be used as a tool for counselors in carrying out their professional duties. This training activity is a similar training that will be carried out at SMKN 62 Lenteng Agung School, so that knowledge and mastery of skills can be improved.